TUBERCULOUS ABDOMINAL AORTIC ANEURYSM – AN UNCOMMON ASSOCIATION WITH VERTEBRAL TUBERCULOSIS - Muhammad Jamil; Rashid Usman (Journal of University Medical & Dental College, 2016)
ABSTRACT: Tuberculosis of the spine is one of the common sites of extra pulmonary tuberculosis. Left untreated it not only causes destruction of spine but concomitant spread to surrounding important structure can be disastrous. Infected aortic aneurysm secondary to tuberculosis usually results from direct extension of the disease from the neighbouring vertebral bodies. It results in weakening of the aortic wall with subsequent aneurysmal dilatation which can rupture and prove fatal. It is a life threatening disease if left untreated or inadequately treated. Considering the high prevalence of tuberculosis in our country, we stress the importance of early recognition and prompt surgical intervention to save life. We report our experience of 6 cases of tuberculous abdominal aortic aneurysms. They were treated with a combination of surgical debridement, aortic replacement with graft and anti-tuberculosis chemotherapy.